1982
DOI: 10.1161/01.cir.66.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary atresia and intact ventricular septum: surgical management based on a revised classification.

Abstract: and premature closure of foramen ovale. Myocardial sinusoids and coronary arteriovenous fistula serving as outflow channel. Am Heart J 70: 476, 1965 24. Steeg CN, Ellis K, Bransilver B, Gersony W: Pulmonary atresia and intact ventricular septum complicating corrected transposition of the great vessels. Am Heart J 82: 382, 1971 entirely overgrown by hypertrophied myocardium. With this appreciation of the variety of ventricular morphology encountered, we have reviewed the results of our surgical management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(65 citation statements)
references
References 15 publications
4
61
0
Order By: Relevance
“…In patients who have tripartite right ventricle 4 , with a patent infundibulum 18 , moderate ventricular hypoplasia at most, and coronary circulation not depending on the right ventricle [6][7][8] , this technique promotes efficient decompression of the ventricular cavity, stimulating its growth 14,19 . Therefore, some potential surgical complications, which may occur in this type of disease, may be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who have tripartite right ventricle 4 , with a patent infundibulum 18 , moderate ventricular hypoplasia at most, and coronary circulation not depending on the right ventricle [6][7][8] , this technique promotes efficient decompression of the ventricular cavity, stimulating its growth 14,19 . Therefore, some potential surgical complications, which may occur in this type of disease, may be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Its morphological spectrum is broad with cases ranging from extremely hypoplastic tricuspid valves and right ventricles to ventricular cavities of almost normal dimensions [2][3][4] . Ebstein's anomaly of the tricuspid valve and extreme ventricular dilation have also been reported, and they are associated with a poor prognosis 5 .…”
Section: New Percutaneous Techniques For Perforating the Pulmonary Vamentioning
confidence: 99%
“…These results suggested that the growth of the right ventricle was commensurate with the physical growth of the patients, and these results are consistent with those in previous reports. 1,3,16,21 Hanley and colleagues' indicated in their prospective multiinstitutional study that the Z-value of the tricuspid valve did not change during the follow-up period of the patients whose right ventricle-to-pulmonary artery continuity had been established at the initial palliation. Similar to our findings, their study also suggested that the diameter of the tricuspid valve enlarged commensurate with the physical growth of the patients whose right ventricular outflow tract had been initially reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, concerns persist regarding application of Simpson's rule to these small and often distorted ventricles. 12 The RVI described in the present report is a modification of the morphologic measurements of Zuberbuhler and Anderson!. These authors related measurements of the TVA, RV inlet and RV outlet to their left ventricular counterparts in order to obtain a meaningful comparison of pathologic specimens.…”
mentioning
confidence: 93%